2012
DOI: 10.5296/ijafr.v2i2.2525
|View full text |Cite
|
Sign up to set email alerts
|

The board of directors and the corporate tax planning: Empirical Evidence from Tunisia

Abstract: Our study represents the first attempt to investigate whether board of directors" attributes have an impact on corporate tax planning in a developing country. Using a sample of 32 companies listed on the Tunisian stock exchange market from 2000 to 2007, results indicate that duality and diversity on the board of directors significantly influences tax planning. Duality exhibits a negative relation with effective tax rates. However, diversity on the board shows a positive association. We don"t find relations bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
12
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 44 publications
4
12
0
2
Order By: Relevance
“…Descriptive statistics show that board size ranges from 4 to 12 directors with an average of 9. On average 83% of the directors are external, this result is similar to that of Aliani and Zarai (2012) which showed that the percentage independent directors in the board is on average 81% in Tunisian companies. This panel shows that on average 88% of members of the Audit Committee are independent.…”
Section: Regression Model Specificationssupporting
confidence: 80%
See 1 more Smart Citation
“…Descriptive statistics show that board size ranges from 4 to 12 directors with an average of 9. On average 83% of the directors are external, this result is similar to that of Aliani and Zarai (2012) which showed that the percentage independent directors in the board is on average 81% in Tunisian companies. This panel shows that on average 88% of members of the Audit Committee are independent.…”
Section: Regression Model Specificationssupporting
confidence: 80%
“…This result is corroborated by Wan and Wan (2009), which showed no relationship between the proportion of outside directors and the best quality of the information disclosed. Zemzem and Ftouhi (2013) and Aliani and Zarai (2012) have not confirm their hypothesis of the impact of outside directors on the level of tax aggressiveness. This result is corroborated with Ghosh et al (2010) and Abed et al (2012) who have not found an association between board independence and some proxies of earnings management.…”
Section: Board Independencementioning
confidence: 91%
“…Peran komisaris independen dalam suatu perusahaan sangatlah penting. Komisaris independen melakukan pengawasan terhadap manajemen akibat dari adanya konflik agensi dalam perusahaan (Jensen dan Meckling, 1976;Khaoula dan Ali, 2012;Zemzem dan Ftouhi, 2013), selain itu komisaris independen juga harus mampu melakukan pengawasan terhadap keputusan dan tindakan yang akan mempengaruhi masyarakat secara keseluruhan (Ibrahim, Howard dan Angelidis, 2003;Rose, 2007 Hasil penelitian ini memberikan dukungan pada aplikasi teori legitimasi dan teori agensi. Hasil penelitian ini dapat dijadikan sebagai bahan referensi penelitian selenjutnya yang ingin memperdalam penelitian mengenai hubungan corporate social responsibility, komisaris indepenedn dengan perpajakan.…”
Section: Pendahuluanunclassified
“…Tindakan agresivitas pajak merupakan suatu upaya yang dilakukan manajemen untuk kepentingannya sendiri dengan harapan akan memperoleh bonus dari pemegang saham, dengan memanfaatkan kekayaan penegang saham (Lanis dan Richardshon, 2011;Suyanto dan Supramono, 2012). Kehadiran komisaris independen dalam dewan komisaris mampu meningkatkan pengawasan kinerja direksi dan manajemen (Fama dan Jensen, 1983;Khaoula dan Ali, 2012;Zemzem dan Ftouhi, 2013).…”
Section: Pengaruh Komisaris Independen Terhadap Agresivitas Pajak Perunclassified
“…Previous studies have returned conflicting findings on the effect of board independence on effective tax rates. For instance, Khaoula and Ali (2012) in a study of 300 S&P firms for periods 1996-2009 obtained results showing that board independence improves tax practices. In other words board independence increases effective tax rates.…”
Section: Board Independence and Effective Corporate Tax Ratesmentioning
confidence: 99%